Peri-procedural Outcome of Small Vessel Coronary Stenting (Bangladesh Heart Journal, 2016)
Background: Among all percutaneous coronary interventions (PCIs), 30 to 40% involve small coronary arteries. Small vessel PCI has historically been associated with poor outcome in terms of coronary artery dissection, acute vessel closure, myocardial infarction, emergent coronary bypass grafting, and restenosis, but the scenario has been changing in recent years. The outcome of small vessel coronary intervention in Bangladeshi population is largely unknown.Objectives: The study was carried out to assess and compare the immediate outcome of PCI in small vessels with that in large vessels.Methods: This prospective, comparative study involved 100 patients undergoing PCI with stent implantation; group I constituted 50 patients having target vessel diameter of 3.0 mm. Immediate outcome of PCI was compared between the two groups. Angiographic, procedural and clinical successes were assessed. Acute complications e.g. major adverse cardiac events (MACE), arrhythmia, hemorrhage, pericardial tamponade, coronary dissection, no flow, vessel rupture and shock were observed.Results: No statistically significant differences in baseline clinical characteristics existed between the two groups. Favourable outcomes were observed in both groups. Angiographic success was 100% in group I, as well as, in group II; procedural and clinical success was 94% vs. 98%, and 90% vs. 94% in small and large vessel groups respectively (p> 0.05). Complications were infrequent in both groups. Also, no statistically significant difference was found in duration of hospital stay post-procedure between group I and group II.Conclusion: Small vessel coronary stenting may be safe and effective. However, these findings require further study involving larger population and long term follow up.Bangladesh Heart Journal 2015; 30(1) : 22-26